BERPIKIR DALAM PENDIDIKAN: (SUATU TINJAUAN FILSAFAT TENTANG PENDIDIKAN UNTUK BERPIKIR KRITIS) - M. Haviz (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2009)
his article is a study about how to think in education. Thinking in education should be integrated in process of learning at colleges. In philosophy, thinking in education is one of means of education for critical thinking. Effectively, thinking in education used to study some problems in education. Thinking in education is metacognition. As a part metacognition, critical thinking applied in college will produced a high quality outcomes. In other words, learning process in colleges wich involved lecturers and students interaction if and appropriate process of building the critical thinking pattern. This pattern will effective if the process is formed integratedly the college policies. Since it will affect to all of educational aspect. It is hopped the result of critical thinking in education will be able to help people in drawing a conclusion as well as applying it in their real life.Kata kunci: thinking, critical thinking, effective, education